Investigation of Performance of a Dual-Chamber Microbial Fuel Cell at Varying PH - Jahan, Sk Ismath Ara; Chanda, Rajesh Kumar; Biswas, Biplob Kumar (Chemical Engineering Research Bulletin, 2023)
One of the recent talked-about issues is zero-carbon emission for ensuring sustainable development. Microbial fuel cell (MFC), a bioelectrochemical process, has attracted much attention due to its potential to be an alternative renewable energy source that can reduce carbon dioxide and methane emission as well. An additional benefit of MFC is that it is aptly capable of treating wastewater. Moreover, this technology is considered to be cheaper and poses no negative impact on environment. In this research a dual-chamber microbial fuel cell was constructed using low-cost and locally available materials. The designed dimension of each chamber was 30.5 cm × 20 cm × 20 cm where working volume was set as 5 L due to ease of handling. The MFC was operated using cow dung substrates, which were collected from the nearby village of Jashore University of Science and Technology campus. The wastewater used in this research was collected from the drain of the same campus (23.23424°N, 89.12609°E). Each set of experiment was conducted for two weeks (14 days) at a stretch. Considering bioelectricity production by the MFC, cow dung was found to be effective. Maximum power (0.8 mW) was produced in a single day during the experiment at a substrate concentration of 25 g/L. The cow dung along with the collected wastewater was investigated to find the effect of factors such as pH. Experiments were performed at varying pH (7, 8 and 10) at room temperature for 14 days. The maximum extent of current density (270 mA/m2), power density (167 mW/m2), and voltage (881 mV) were found at pH 8 by using drainage wastewater as a feedstock in combination with cow dung from the microbial fuel cell. The treatment of wastewater using the MFC demonstrated varied efficacy, achieving COD removal rates of 88.3% at pH 7, 90.2% at pH 8, and 84.4% at pH 10. The results highlight the MFC's potential as a dual-purpose technology for effective pollutant removal and bioelectricity generation, particularly at an optimal pH of 8. These findings underscore the MFC's potential for dual-use in pollutant removal and energy generation, contributing to energy security. Chemical Engineering Research Bulletin 23 (2023): 52-56